Pola Relasi Sosial Elit Tradisional: Kasus Desa Rana Mbeling, Kabupaten Manggarai Timur, NTT - Jehamat, Lasarus (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2011)
Social relationship between tua golo and tua teno have typical pattern. As we know that the relationship pattern between tua golo and tua teno have the character of subordinative and coordinative. Relationship having the character of subordinative happened because social structure of society of Manggarai as a whole place one of the social elite on course above from each other. Here is, tua golo have position which is important to be compared with tua teno. Because tua golo is the head of kampong and tua golo determining the position of tua teno as institute managing or dividing land. The implication of the relationship model like this is tua teno have to ask permission of tua golo in every activity related to custom and land. Whereas relationship having the character of coordinative happened when tua golo and tua teno sit with in one forum to discuss things related to problem of kampong or other of social problem. Â Kata Kunci: Elit, Relasi Sosial, Konflik